Arsenic Contamination of Groundwater a Grave Concern: Novel Clay-based Materials for Decontamination of Arsenic (V) - Dwivedi A.; Tiwari D.; Lee S.M. (My University, 2025)
Arsenic is a highly toxic element, and its contamination is widespread around the world. The natural materials with high selectivity and efficiency toward pollutants are important in wastewater treatment technology. In this study, the mesoporous synthetic hectorite was synthesized by facile hydrothermal crystallization of gels comprising silica, magnesium hydroxide, and lithium fluoride. Additionally, the naturally available clay was modified using zirconium at room temperature. Both synthetic and modified natural clays were employed in the removal of arsenate from aquatic environments. The materials were fully characterized by scanning electron microscope (SEM), X-ray diffraction (XRD), and Fourier transform-infrared (FT-IR) analyses. The synthesized materials were used to remove arsenic (V) under varied physicochemical conditions. Both materials, i.e., Zr-bentonite and Zr-hectorite, showed high percentage removal of arsenic (V) at lower pH, and the efficiency decreased in an alkaline medium. The equilibrium-state sorption data agrees well with the Langmuir and Freundlich adsorption iso-therms, and the maximum sorption capacity is found to be 4.608 and 2.207 mg/g for Zr-bentonite and Zr-hectorite, respectively. The kinetic data fits well with the pseudo-second order kinetic model. Furthermore, the effect of the background electrolytes study indicated that arsenic (V) is specifically sorbed at the surface of these two nanocomposites. This study dem-onstrated that zirconium intercalated synthetic hectorite as well as zirconium modified natural clays are effective and efficient materials for the selective removal of arsenic (V) from aqueous medium. © 2023 The Korean Society of Industrial and Engineering Chemistry. All rights reserved.